The Effect of Maternal Age on the Incidence of Major Malformations and Operations in Children with Down Syndrome - Elif YILMAZ GULEC; Alper GEZDIRICI (Medeniyet Medical Journal)
Objective: Children with Down syndrome have a high incidence of major malformations and corrective surgery. Some patients do not need any surgery, while some cases are operated for several indications. There are few studies investigating the effect of maternal age on the phenotype of these children, despite the fact that increasing maternal age is a known risk factor for giving birth to Down syndrome. We aimed to investigate the incidence of surgery for major malformations and disorders in children with Down syndrome and its relationship with maternal age at birth. Methods: We revised the records of 218 children with Down syndrome for maternal age at birth and for surgical interventions. Results: There were 84 children who had at least one operation with 38.5% incidence. A total of 49 children had cardiac surgery, 16 had gastrointestinal, 17 had head and neck area, 12 had ophthalmological, 12 had genitourinary, 5 had hernia, and 2 had orthopedic surgeries. The mean maternal age was 32.7 (minimum: 15; maximum: 44), and there was no significant difference between operated and non-operated groups for mean maternal ages (32.41 and 32.93, respectively; p=0.89). For any type of surgery, there was no significant difference between the groups with maternal ages 35 and over and those under 35. Conclusions: Maternal age at birth has no effect on the incidence of malformations and the probability of operation in Down syndrome.